Hydropower, a Good Alternative for Nepal: Challenges and Approaches - Garcia, John C. (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
Although Hydropower development is a good option for Nepal, there are serious challenges to the successful construction and operations of such facilities. This article briefly addresses why hydropower development is appropriate for Nepal as well as some of the more important social and environmental challenges. The author also makes suggestions to approach these challenges.Key words: Hydropower; social and environmental impacts; landslides; sediments; biodiversity; poverty alleviation; fisheries; compliance; community relations; reporting; NepalHydro Nepal: Journal of Water, Energy and Environment Vol. I, Issue No. 1 2007, pp. 7-14